The large eruption 4.2 ka cal BP in Cerro Blanco, Central Volcanic Zone, Andes: Insights to the Holocene eruptive deposits in the southern Puna and adjacent regions - Fernande Turiel, José Luis (2019)
Fil: Fernández Turiel, José Luis. Consejo Superior de Investigaciones Científicas. Instituto de Ciencias de la Tierra Jaume Almera; España